Knowledge and its Associated Factors on Autonomic Dysreflexia among Medical Officers of Selected Hospital of Nepal - Adhikari, Pratima; Banjade, Rekha; Bhusal, Mina Kumari; Bhattarai, Amit (Journal of College of Medical Sciences-Nepal, 2025)
Background Autonomic Dysreflexia (AD) is a life-threatening complication of spinal cord injury above T6 level. It is devastating consequences that may lead to stroke, hypertensive crisis and seizure and trigger by simple noxious stimuli like full bladder, poor bowel clearance and restrictive clothes. So, doctor`s role in AD is early identification, treatment and prevention. This study aimed to assess knowledge regarding Autonomic Dysreflexia among medical officer. Methods An analytical cross-sectional study was carried out among 60 Medical Officers working in a selected hospital. Data were collected using census method with a structured self-administered questionnaire and analysed in SPSS version 16 by using descriptive and inferential statistics. Results The study findings revealed that the mean age of respondents was 27.90±1.95 years. More than half of the respondents (58.3%) had more than 10 years of working experience. Half of them (51.7%) came into contact with a spinal cord injury patient, and 48.3% were not. Almost all (98.3%) had not participated in in-service education on AD. Mean knowledge score was 16.45±3.34, where more than half (58.3%) of respondents had poor knowledge, and only 41.7% had good knowledge regarding AD. There is significant association between levels of knowledge with working area, with respondents working in the emergency department. Conclusions The study revealed that medical officers had poor level of knowledge of Autonomic Dysreflexia. Limited formal training was evident among respondents. Regular training and continuing education are recommended to enhance healthcare providers’ ability to recognize, prevent, and manage this potentially life-threatening condition.